Genetic variability for ginning outturn and association among fiber quality traits in an upland cotton global germplasm collection - Hayat, Khezir; Bardak, Adem (Penerbit Universiti Kebangsaan Malaysia, 2020)
Gossypium genus is the main source of natural fiber all over the world. Limitations in conventional breeding program for genetic improvement are due to the complexity and limited knowledge about economically important traits. A diverse germplasm was screened at East Mediterranean Transitional Zone Agricultural Research Institute of Kahramanmaras and at farmer field in Diyarbakir Turkey during 2016 to assess variation for ginning outturn and fiber quality. The gene pool was consisted of global collections namely Acala Maxa, Fibermax810 and Stoneville-453 derived from USA, Delcerro (Venezuela), Carmen (Australia), Taskent-6, Samarkand Uzbek (Uzbekistan), Allepo-40 (Syria), Albania-6172 (Albania), Lachata, Nata (Spain), NSCH777 (India) and elite cultivars from Turkey including Carla, Nazilli84S, Ozbek142 and Fantom. Analysis of variance showed highly significant differences among genotypes for all traits on pooled data basis. Correlation analysis showed significant relationship among fiber traits such as fiber length, fiber strength and micronaire. It was concluded that some genotypes can be used as potential parents in breeding such as AB-80 and BA440 for increasing lint percentage, YB-230 and Flora for fiber length, and Delcerro and Menderes for fiber strength.